Community responses to Jihadist mobilisation in Central Mali - Rupesinghe, N (2024)
Why do some communities join and strike alliances with jihadist insurgents, while others oppose through violent resistance? Why do communities shift their responses to insurgency over time? Drawing on 190 interviews collected during fieldwork in Bamako between September 2021- April 2022, I investigate community responses to jihadist mobilisation across six rural communes. The findings challenge conventional explanations which emphasise ethnic grievances, religious conviction and materialist incentives. Instead, I argue local cleavages, war dynamics and social processes shape community responses. In deeply divided contexts, groups joined or allied with jihadists to settle longstanding rivalries and enduring, unresolved conflicts. Faced with violence, powerholders leverage their repressive capacities to violently resist, whether through military partnerships, village brigades or grassroots militias. It was micro-level grievances around land, power and status, rather than national-level ones that drove these choices. Second, war dynamics – the coercive repertoires used by armed actors – help explain why communities shift their responses over time. When state or militia violence is directed against ethnic communities accused of being complicit with jihadists, those groups which accommodated jihadists, seek out alliances with them for protection. Finally, community choices are influenced by social processes of war, including ambiguity around identity and the rupture of social relations. Many communities, regardless of identity, tolerated jihadists for some time before adopting violent resistance. Once the wartime identity of ‘jihadist’ was constructed as a threat from ‘within’ and along ethnic lines, violent behaviours in the name of defence were legitimated. Social rupture, which involved the breakdown of existing norms of reciprocity and exchange, made acts of opposition possible. While local cleavages shaped initial decisions, factors which are endogenous to the war also influence community behaviours. The findings suggest local logics of mobilisation for and against jihadist insurgents often have little to do with national-level stakes or ideology.